Surviving Volcanic Environments—Interaction of Soil Mineral Content and Plant Element Composition - Baillie, Christin-Kirsty; Kaufholdt, David; Meinen, Rieke; Hu, Bin; Rennenberg, Heinz; Hänsch, Robert; Bloem, Elke (Frontiers in Environmental Science, 2018)
Different plant species were investigated from two Aeolian Islands located in close vicinity, one with fumarolic activity (Vulcano) and one without (Lipari). On Vulcano, elevated concentrations of SO2/H2S determined in ambient air indicated the need of plants to adapt to harmful sulphur concentrations by detoxification strategies. The current study was focused on evaluating the element composition of plant leaves in relation to soil mineral contents. The soil of Volcano was characterised by a significantly lower pH on all three sampling sites as well as very high amounts of sulphur and plant available sulphate due to volcanic activities, compared to Lipari. By contrast, a general difference in the composition of trace elements in the soil was not observed between the islands, apart from arsenic, which was increased at all three sampling sites on Vulcano. Element accumulation in the leaves differed between the two islands. The tested species showed a significant higher accumulation of numerous elements (Al, B, Fe, K, Mg, Mn, Ni, and Zn) on Vulcano compared to Lipari, while excluding Ca and Mo. These differences in element accumulation in the leaves between the islands may be caused by the lower soil pH on Vulcano. Extreme sulphur accumulation was found for all tested species on Vulcano, but was lower in woody species with higher dry matter content compared to herbaceous species with lower dry matter content. This caused a significantly negative correlation between plant sulphur and dry matter content. From these results, it is concluded that species with higher dry matter contents possess a more effective protection against extreme sulphur accumulation. Strategies to cope with other potentially toxic elements in the soil ranged from exclusion to hyper-accumulation. Hierarchical cluster analyses of the leaf element content revealed a clear separation between two groups: First, herbaceous perennial plants as strong accumulators; and second, woody perennial plants such as shrubs or trees as less strong accumulators, with the primordial species Fumaria capreolata representing an outside group.